Penyelesaian Sengketa pada Merek yang Telah Dialihkan: Studi Kasus Merek Denza - Prasojo, Andreas; Zulfa Aulia, M.; Windarto, Windarto (Zaaken: Journal of Civil and Business Law, 2026)
This research concerns the resolution of the Denza trademark dispute that has been transferred in the case of BYD vs. PT. Worcas. This research aims to analyze the impact of the transfer of Denza trademark rights based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications in Indonesia after the transfer of trademark rights. The problem formulation includes a legal analysis of the dispute reviewed based on Indonesian trademark law and the legal implications of the transfer of trademark rights. The research method uses a normative juridical approach with a study of primary legal materials of the Law on Trademarks and secondary materials from IPR literature. The results of this research are first, that the transfer of rights has been recorded in the DJKI and is constitutive, second, the court determined that the lawsuit was an error in persona which caused a formal defect in the lawsuit. With the transfer of rights, the lawsuit was rejected due to an error in persona, making it difficult for multinational companies to register their trademarks in Indonesia. The government should also strengthen the mechanism for recognizing well-known trademarks to prevent trademark squatting.